IMPLEMENTASI AYAT-AYAT TENTANG PINJAMAN DALAM PERSPEKTIF EKONOMI ISLAM - Pradana, Aldo Robby (Commodity : Jurnal Perbankan dan Keuangan Islam, 2024)
Loans are one of the human needs from ancient times to the present. There are many reasons why someone borrows something, especially property. Loans or qard are the most basic concept of loans according to Islamic law where no profit may be taken from this lending transaction. This study uses a qualitative literature method that emphasizes sources from books, articles, or other notes. This study emphasizes a comprehensive explanation of the concept of a loan or qard agreement along with the conditions that must be met. The owner of the funds is not allowed for any reason to ask for additional assets lent to others. However, the party being lent may provide additional loans sincerely if there is no coercion from other parties, including the lender.